The breakfast club - Tanen, Ned.; Hughes, John, 1950-2009.; Estevez, Emilio, 1962-; Gleason, Paul, 1944-2006.; Hall, Anthony Michael; Nelson, Judd.; Ringwald, Molly; Sheedy, Ally.; Kapelos, John.; Allen, Dede.; Forsey, Keith; Del Ruth, Thomas, 1942-; et al. (Universal City, CA : Universal Studios Home Entertainment, 2008)
Five high school students-- a Rebel, an Athlete, a Brain, a Princess and a Basketcase-- find themselves thrown together serving a Saturday morning detention. They do not have much in common, except giving up their day, sitting in the school library, and writing an essay for the principal. At first, they argue and hate each other, but after smoking some of the Rebel's marijuana, they begin to pour their hearts out to each other. They talk about their fears, secrets, deepest emotions, and problems.
Edition from container.
Originally released as a motion picture in 1985.
Special features: "Sincerely yours" featurette; "The most convenient definitions : the origins of the Brat Pack" featurette; feature commentary with Anthony Michael Hall and Judd Nelson; theatrical trailer.
Director of photography, Thomas Del Ruth ; editing, Dede Allen ; music composer, Keith Forsey.
Emilio Estevez, Paul Gleason, Anthony Michael Hall, Judd Nelson, Molly Ringwald, Ally Sheedy, John Kapelos.
MPAA rating: R.
Keywords: High school students -- Illinois -- Drama; School discipline -- Illinois -- Drama; Teenagers -- Drug use -- Illinois -- Drama; Teenagers -- Social networks -- Illinois -- Drama; Illinois -- Drama; Comedy films; Coming-of-age films; Teen films; Feature films; Video recordings for the hearing impaired; Fiction films